(untitled) (LACCEI, 2024)
Globalization, the revolution of new information technologies and digital entrepreneurship, has triggered a growth in the tourism sector, expanding to new agents and regions. This situation motivates to conduct research on the challenges and changes in the industry, which is why the purpose of this paper is to analyze the importance of digital entrepreneurship leveraged on technologies and innovation, and its relevance in the economic revival in the tourism industry in Colombia. For its scope (1), we start from a bibliometric analysis supported by the tools VOSviewer 1.6.19, Biblioshiny R and Vantage Point, of 364 documents indexed in Scopus and Web of science, based on the equation (("entrepreneurship*" OR "digital entrepreneurship*" OR "artificial intelligence") AND ("Tourism* Entrepreneurship*" OR "Tourism*")) [2] As a complement, we analyzed technological tools used in the sector, its value proposition and business model. The results show an average growing trend of 43.32%, with the highest scientific production for the year 2022 (121 articles). Similarly, the United Kingdom and China are the countries with the highest level of production and collaborative work. Entrepreneurship, Tourism and Innovation are ranked as Driving Themes, reflecting their importance in recent research. Finally, innovation is a relevant factor in the processes of digital entrepreneurship, influencing in a disruptive way the growth of the tourism industry.